Assessing the Carbon Sequestration Potential of Ultramafic Rocks in the Kolaka Ophiolite Complex, Southheastern Sulawesi: A Petrographic, Geochemical, and Mineralogical Study - Syahrul; La Ode Dzakir; Riska; Rio Irhan Mais Cendra jaya; Masri (UIR PRESS, 2025)
Climate change has prompted significant global interest in carbon sequestration technologies, particularly using geological formations. This study investigates the potential of ultramafic rocks from the Kolaka Ophiolite Complex in Southeast Sulawesi for carbon sequestration, focusing on the mineralogical, petrographic, and geochemical characteristics that enhance their reactivity with CO₂. The research involved petrographic and mineragraphic analyses of 15 peridotite samples, geochemical measurements via X-ray fluorescence (XRF), and mineral characterization using scanning electron microscopy (SEM). The results revealed that Kolaka's ultramafic rocks, particularly harzburgite and lherzolite, exhibit moderate to high serpentinization, which enhances their reactivity with CO₂. Key minerals such as olivine, pyroxene, and serpentine, rich in magnesium, calcium, and iron oxides, demonstrate significant potential for mineral carbonation. Secondary minerals like magnesite and brucite were identified as products of carbonation, reinforcing the rocks' ability to act as carbon sinks. The discussion highlights that serpentinized peridotites are more effective for carbon sequestration than unaltered ones due to increased mineral reactivity. The presence of magnesite and Cr-Fe-rich carbonates, alongside serpentine veins, indicates that fluid-rock interactions have promoted ongoing carbonation processes. The Kolaka ultramafic rocks, therefore, hold strong potential for long-term carbon storage, offering a promising solution for reducing atmospheric CO₂ levels